Role of Early Application of Pressure Garments following Burn Injury and Autografting. Issue 2 (February 2019) - DeBruler, Danielle M.; Baumann, Molly E.; Blackstone, Britani N.; Zbinden, Jacob C.; McFarland, Kevin L.; Bailey, J. Kevin; Supp, Dorothy M.; Powell, Heather M.
Abstract : Background: Pressure garment therapy, used for reduction of postburn scarring, is commonly initiated after complete healing of the wound or autograft. Although some clinicians have suggested that earlier treatment may improve outcomes, the effect of early initiation of therapy has not been studied in a controlled environment. Methods: Full-thickness burns were created on red Duroc pigs, burn eschar was excised, and the wound bed was grafted with split-thickness autografts. Grafts were treated with pressure garments immediately, 1 week (early), or 5 weeks (delayed) after grafting with nontreated grafts as controls. Scar morphology, biomechanics, and gene expression were measured at multiple time points up to 17 weeks after grafting. Results: Grafts that received pressure within 1 week after grafting exhibited no reduction in engraftment rates. Immediate and early application of pressure resulted in scars with decreased contraction, reduced scar thickness, and improved biomechanics compared with controls. Pressure garment therapy did not alter expression of collagen I, collagen III, or transforming growth factor β1 at the time points investigated; however, expression of matrix metalloproteinase 1 was significantly elevated in the immediate pressure garment therapy group at week 3, whereas the delayed pressure garment therapy and control groups approached baseline levels at this time point. Conclusions: Early application of pressure garments is safe and effective for reducing scar thickness and contraction and improving biomechanics. This preclinical study suggests that garments should be applied as soon as possible after grafting to achieve greatest benefit, although clinical studies are needed to validate the findings in humans. Abstract : Supplemental Digital Content is available in the text.